CHEMICAL COMPOSITION OF THREE TREE FODDERS AND EFFECT IN CONTROL Haemonchus contortus AND CHANGE OF BODY WEIGHT IN KIDS - Castro-León, Yesenia; Olivares Pérez, Jaime; Rojas-Hernández, Saúl; Villa-Mancera, Abel; Valencia-Almazán, Ma Trinidad; Hernández-Castro, Elías; Córdova-Izquierdo, Alejandro; Jiménez-guillen, Régulo (Ecosistemas y Recursos Agropecuarios, 2015)
The objective was to evaluate the activity against Haemonchus contortus three tanniferous foliage trees in Creole male kids experimentally infected with a dose of 350 larvae (L3) / kg body weight. Twenty Creole kids 12 ± 2.0 kg of body weight (BW) were randomly distributed in four treatments: T1 = control without foliage, and the addition of fresh foliage (10% of the dry matter of the total diet) of Guazuma ulmifolia (T2), Pithecellobium dulce (T3) and Acacia cochliacantha (T4). For sixty days activity against H. contortus foliage was evaluated by reducing the elimination of eggs per gram of feces, plus the elimination of eggs was associated with the concentration of blood cell pack, dry matter intake and weight change of animals. The data of the evaluated variables were analyzed in a completely randomized design and Tukey test for comparison of means (p <0.05). Foliage tannins of P. dulce and A. cochliacanta were more effective (p <0.0406) in the control of H. contortus with minor elimination of eggs (1.48 and 1.18 Log10 / g of feces) respectively. The hematocrit was different (p <0.001) mainly in hemoglobin, erythrocytes, lymphocytes and eosinophils; the dry matter intake and change total body weight was higher (p <0.003) in kids who received the foliage of P. dulce (T3) with 621.5 g per day and 2.4 kg, respectively. Was concluded the tannins of foliage fresh of P. dulce and A. cochliacantha have the potential to control Haemonchus contortus without affecting health and productive response Kids.